Clinical correlates of emotion dysregulation in Down syndrome: a comparative study - Fucà, Elisa; Mongiovì, Valentina Maria; Vicari, Stefano; Costanzo, Floriana (Frontiers in Psychology, 2025)
IntroductionEmotion regulation is crucial for mental health and adaptive psychological functioning. Despite growing interest in emotion dysregulation (ED) in individuals with intellectual disability (ID), little is known about its association with neuropsychological and psychopathological profiles in children and adolescents with Down syndrome (DS), the most frequent genetic cause of ID. This study aimed to compare the neuropsychological profile, psychopathological symptoms, and sleep disturbances of children with DS with and without ED.MethodsData were retrospectively collected from a database. The final sample included 214 participants (6–18 years): 69 with co-occurring ED and 145 controls without ED, with groups balanced for age and sex. Emotional/behavioral difficulties and sleep problems were assessed through parent-report questionnaires and clinical interviews. Language abilities and visual-motor integration skills were evaluated by standardized tests.ResultsChildren with co-occurring ED exhibited significantly worse visual-integration and motor coordination skills than children without co-occurring ED. Moreover, they displayed more psychopathological symptoms ascribable to both externalizing and internalizing problems. Finally, children with ED exhibited more sleep difficulties associated with insomnia and parasomnias.ConclusionThese results emphasize the need to consider ED in assessment and interventions, as it can significantly impact neuropsychological development and overall wellbeing.